2001
DOI: 10.1164/ajrccm.164.6.2010115
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Effects of Vitamin A on Surfactant Synthesis in Nitrofen-induced Congenital Diaphragmatic Hernia in Rats

Abstract: Congenital diaphragmatic hernia (CDH) is a major cause of refractory respiratory failure in the newborn. Besides pulmonary hypoplasia, the pathophysiology of CDH also includes surfactant deficiency. Vitamin A (vit A) is important for various aspects of lung development. We hypothesized that antenatal treatment with vit A would stimulate lung surfactant synthesis in experimental CDH induced in rats by maternal ingestion of the herbicide nitrofen (2,4-dichloro-phenyl-p-nitrophenyl-ether) on Day 12. Fetuses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 43 publications
1
44
2
Order By: Relevance
“…No differences between groups were detected in CCSP, SP-C and PAS-stained cells score. Contradictory results about lung maturity and surfactant status in CDH animal models have been published, with studies demonstrating that the CDH lung is surfactant deficient (51)(52)(53) and others indicating no change in alveolar surfactant composition, un- changed or even increased surfactant protein expression (54)(55)(56)(57). However, one of the most recent studies performed with human CDH fetuses demonstrated that surfactant maturation is not delayed (54).…”
Section: Discussionmentioning
confidence: 99%
“…No differences between groups were detected in CCSP, SP-C and PAS-stained cells score. Contradictory results about lung maturity and surfactant status in CDH animal models have been published, with studies demonstrating that the CDH lung is surfactant deficient (51)(52)(53) and others indicating no change in alveolar surfactant composition, un- changed or even increased surfactant protein expression (54)(55)(56)(57). However, one of the most recent studies performed with human CDH fetuses demonstrated that surfactant maturation is not delayed (54).…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantage of intratracheal administration of vitamin A with surfactant would be to achieve a direct local effect with decreased systemic side effects. This could possibly occur through the effect that vitamin A has on stimulation of surfactant synthesis (20,21). This is, however, unlikely because it happened independently from changes in lung compliance.…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by a series of experiments undertaken in the nitrofen rat model for CDH. This study was inspired by the promising results obtained by the administration of glucocorticoids, thyroid hormone or vitamin A to nitrofen-treated rats (13,16,17,(25)(26)(27). In our previous study, we have shown the expression of the nuclear hormone receptors in human lung from 13.5 wk until term with no change in localization throughout development (21).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic RAR␣/RXR␣ and RAR␣/␤ double knockout mice were shown to have lung hypoplasia or agenesis (37)(38)(39). Our collaborative studies in the nitrofen rat model for CDH demonstrated that prenatal administration of vitamin A reduces the incidence of CDH and increases the levels of surfactant protein A and C in the offspring (16,17). In …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation